High‐fat Diet‐induced Intestinal Hyperpermeability is Associated with Increased Bile Acids in the Large Intestine of Mice. Issue 1 (23rd November 2015) - Murakami, Yuki; Tanabe, Soichi; Suzuki, Takuya
Abstract : Metabolic syndrome is characterized by low‐grade chronic systemic inflammation, which is associated with intestinal hyperpermeability. This study examined the effects of 3 high‐fat diets (HFDs) composed of different fat sources (soybean oil and lard) on the intestinal permeability, tight junction (TJ) protein expression, and cecal bile acid (BA) concentrations in mice, and then analyzed their interrelations. C57/BL6 mice were fed the control diet, HFD (soybean oil), HFD (lard), and HFD (mix; containing equal concentrations of soybean oil and lard) for 8 wk. Glucose tolerance, intestinal permeability, TJ protein expression, and cecal BA concentration were evaluated. Feeding with the 3 HDFs similarly increased body weight, liver weight, and fat pad weight, and induced glucose intolerance and intestinal hyperpermeability. The expression of TJ proteins, zonula occludens‐2 and junctional adhesion molecule‐A, were lower in the colons of the 3 HFD groups than in the control group ( P < 0.05), and these changes appeared to be related to intestinal hyperpermeability. Feeding with HFDs increased total secondary BA (SBA) and total BA concentrations along with increases in some individual BAs in the cecum. Significant positive correlations between intestinal permeability and the concentrations of most SBAs, such as deoxycholic acid and ω‐muricholic acids, were detected ( P < 0.05). These results suggest that the HFD‐induced intestinal hyperpermeability is associated with increased BA secretion. The abundance of SBAs in the large intestine may be responsible for the hyperpermeability.